2016
DOI: 10.1080/13548506.2016.1274042
|View full text |Cite
|
Sign up to set email alerts
|

Depression and sleep quality in older adults: a meta-analysis

Abstract: The literature emphasizes depression and poor sleep quality as problems that affect many elderly individuals. However, these problems have been related in few studies and there is no meta-analysis performed so far on this relationship. The present research reviewed the studies performed on the subjective sleep quality in order to understand how it relates to depression in older adults. The review was conducted in January 2016 and comprised publications between 2005 and 2015. Based on the electronic databases W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 27 publications
8
55
1
9
Order By: Relevance
“…In our study, increased time sleeping was associated with small improvements in all mental health outcomes. This is consistent with findings from the US Behavioral Risk Factor Surveillance System suggesting that poor sleep is commonly experienced in the general population, and is associated with mental distress [ 46 ] and depression [ 47 ]. Other studies have highlighted a U-shaped relationship between sleep duration and mental health, with poorer outcomes associated with both short and long sleep duration [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, increased time sleeping was associated with small improvements in all mental health outcomes. This is consistent with findings from the US Behavioral Risk Factor Surveillance System suggesting that poor sleep is commonly experienced in the general population, and is associated with mental distress [ 46 ] and depression [ 47 ]. Other studies have highlighted a U-shaped relationship between sleep duration and mental health, with poorer outcomes associated with both short and long sleep duration [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Poor quality of sleep is in association with anxiety and depression. [31][32][33][34][35][36][37][38][39] Our results share several similarities with Potvin et al's ndings, which reported a signi cant association of PSQI subscales with anxiety, particularly sleep duration in hours, sleep disturbance score, and daytime functioning score. [40] Since sleep is a complex biological process, providing an exact pathophysiological theory as a justi cation of reported correlations between poor sleep quality, depression and anxiety have been a subject of controversy.…”
Section: Discussionsupporting
confidence: 86%
“…Participants with current depressive symptoms will show poorer sleep quality than participants without current or historical depression. consecutive days and nights of wrist actigraphy, than participants without current or historical depression (Naismith et al, 2009(Naismith et al, , 2011 Pittsburgh Sleep Quality Index), participants with current depressive symptoms will report a greater amount of sleep problems than participants without current or historical depression (Foley et a., 1995;Becker, Jesus, Joao, Viseu, & Martins, 2017).…”
Section: Hypothesis Ii: Depressive Symptoms Are Connected To Poorer Smentioning
confidence: 99%